METHODS EMPLOYED IN RESEARCH ON THE SPATIAL STRUCTURE OF AGRICULTURE - Kołodziejczak, Anna (Quaestiones Geographicae, 2013)
The research conducted in the field of agricultural geography concerns both, the conditions and factors controlling the spatial structure of rural areas. It includes several lines of study, like an assessment of the natural environment for agricultural purposes, designing land-use maps, examining agricultural suburban zones, model approaches to agriculture, the spatial structure of agriculture, methods of the typology and regionalisation of agriculture, or multi- functionality of agriculture. They make use of a great variety of methods. This article presents methods employed in research on the spatial structure of agriculture. It defines the notion of a spatial structure, the consequences that follow from it, and methodological assumptions. The methods discussed embrace statistical methods of studying the spatial structure of agriculture, those used to determine elements predominating in this structure and to describe its heterogeneity, as well as mathematical and spatial-econometric models.